Benefit of Brown Rice Feeding on Elderly Insomnia - Titiek Hidayati; Nevi Seftaviani; Hastin Munifah T.F.F.S.; Ardhitapramesti A.H.P.; Nurisa Fikriyani L. (International Journal of Public Health Science (IJPHS), 2015)
Difficulty falling asleep or insomnia is one of health problems in elderly. Age is one of the risk factor of insomnia. Tryptophan in brown rice can stimulate the formation of serotonin. Serotonin is a neurotransmitter that causes someone sleeps easily. This research used quasi-experimental design with pretest posttest without control group. Population in this research is 20 elderly persons in Budi Luhur Nursing House unit of Kasihan, Bantul. Result experiment shows that 7 elderly persons have improvement in difficulty falling asleep or insomnia. Improvement of insomnia degree in elderly may be caused by the tryptophan in brown rice. Elderly persons can consume brown rice as alternative food for improving insomnia.